Role of density and resource competition in determining aggressive behaviour in salamanders. (16th April 2015) - Manenti, R.; Pennati, R.; Ficetola, G. F.
Abstract Intraspecific aggression is an important aspect of social behaviour that can significantly affect individual survivorship and population dynamics. Aggressiveness may be particularly important in food‐deprived habitats, like caves, but few studies have investigated behavioural and ecological determinants of aggressiveness and cannibalism in cave vertebrates. In this study, we evaluated the role of density, competition for food, starvation and rearing history under cave‐like conditions in promoting aggression. We performed a behavioural experiment on larvae collected from multiple underground springs and neighbouring streams, and we reared them under two different settings: total darkness and outdoor conditions. Intraspecific attacks were very scarce in hatchlings, and increased after 1 month. Starvation periods and high density clearly increased aggressiveness. Furthermore, aggressiveness strongly increased under competition conditions (presence of other larvae feeding). Aggressiveness increased with age more quickly in larvae from caves than in those from streams. Environmental features typically experienced by cave populations, such as starvation and high density, increase intraspecific attacks and might promote cannibalism. Strong plasticity for aggression may enhance the possibility to successfully colonize and exploit food‐deprived environments where no other predators can survive, such as underground environments.